The API Integrity and Access Control Framework (AIACF): A Zero-Trust Security Model for U.S.-Connected Consumer Platforms - Lamin Saidy,; Abraham Ayodeji Abayomi,; Abel Chukwuemeke Uzoka,; Bolaji Iyanu Adekunle, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
The rapid proliferation of consumer Internet of Things (IoT) devices has exponentially increased the attack surface for cyber adversaries, with Application Programming Interfaces (APIs) serving as critical yet vulnerable integration points within smart ecosystems. This paper introduces the API Integrity and Access Control Framework (AIACF), a comprehensive zero-trust security model designed to fortify API governance for U.S.-connected consumer platforms. AIACF integrates multi-layer authentication, real-time anomaly detection, and role-based access controls to establish continuous, context-aware validation and dynamic threat mitigation. Grounded in zero-trust principles and aligned with national cybersecurity priorities articulated by the National Security Agency (NSA) and Department of Homeland Security (DHS), the framework addresses critical vulnerabilities contributing to API abuse and data breaches. We detail AIACF’s modular architecture, practical deployment strategies, and evaluation metrics, supported by a case study demonstrating its efficacy in reducing unauthorized access and mitigating API-based attacks. The framework’s adaptability and scalability position it as a strategic tool for enhancing the security posture of consumer IoT environments, advancing national efforts to safeguard critical technological infrastructure. Future research directions emphasize the incorporation of advanced machine learning for anomaly detection, scalability optimization, and broader applicability across diverse IoT domains.
Keywords: Zero-Trust Security; API Governance; Multi-Layer Authentication; Anomaly Detection; Role-Based Access Control; Consumer Internet of Things (IoT)